(untitled) (Metallurgy and Foundry Engineering, 2015)
Other than granular and dispersive microstructures, the lamellar microstructure is one of the most-frequently observed traits in the case of metal alloys. This work defines a geometrical model of a lamellar microstructure and presents its stereological relationships as well as our computersimulation results for this model. The applied methodology creates – at least from a theoretical point of view – a series of interesting possibilities in the field of quantitative description of this type of microstructure and examinations of the properties of the parameter estimators that quantitatively characterize it.